Analysis of Lead (Pb) in the Coastal of Kupa Kupa Village, South Tobelo Dictrict, North Halmahera Regency: Analisis Kandungan Timbal (Pb) Pada Perairan Pantai Desa Kupa Kupa, Kecamatan Tobelo Selatan, Kabupaten Halmahera Utara - Sophia N. M. Fendjalang; Krisostomus Rupilu; Silvanus M. Simange; Alfrianti Paparang (Journal of Tropical Fisheries Management, 2022)
Human activities in coastal waters such as transportation, industry, tourism, settlements, and agriculture are the main factors that cause changes in water quality. Changes in water quality can be the beginning of pollution if the value of the water quality parameter has exceeded the seawater quality standard. One form of marine pollution is heavy metal pollution, and the metal most commonly found in coastal waters is lead (Pb). Therefore, the purpose of this study is to analyze the content of lead (Pb) on the coastal of Kupa Kupa Village, South Tobelo District, North Halmahera Regency. In this study, sampling was carried out using the purposive sampling method, where the water samples used were taken at predetermined points along the coastal waters of Kupa Kupa Village, South Tobelo District, North Halmahera Regency. Sampling of seawater was carried out using a sampling pole with a water depth of 5 m, then the samples were analyzed according to SNI 6989.8.2009. The results of the analysis are then described qualitatively. The results showed that the quality of the coastal waters of Kupa Kupa Village ranged from 32 – 34°C, salinity 27 – 34 ppt, pH 8.9 – 9.3, DO 7.88 – 7.91 mg/l, brightness 1 – 5.9 m, and current 0.05 – 0.12 ms-1. Meanwhile, the concentration of lead (Pb) in water in the coastal waters of Kupa Kupa Village, South Tobelo District, which is in the range of 0.50-0.78 mg/L, where this concentration has exceeded the seawater quality standards. Thus, the coastal waters of Kupa Kupa Village have been contaminated with lead metal which will be threatening for the life of marine biota and will also have an impact on human health.